TSP METHOD USING NEAREST NEIGHBOR ALGORITHM AT PT. J&T EXPRESS IN BANDUNG - Anie Lusiani; Siti Samsiyah Purwaningsih; Euis Sartika (LPPM Universitas Bina Bangsa, 2023)
Effectiveness and efficiency are very important for an expedition company in optimizing the delivery of goods by a courier. The Traveling salesman problem (TSP) method using the Nearest Neighbor Algorithm can optimize the delivery of goods to all consumer location points with only one visit in one trip. The purpose of this study is to find the shortest route using the TSP method based on the travel distance data from drop point PT. J&T Express Sarijadi Bandung to all consumer points and back to this drop point. This data is processed using Matlab and Excel Solver software based on the Nearest Neighbor Algorithm. The results of this study show that the TSP method produces the shortest route, which is 1,944 meters. The delivery route generated by this method provides travel distance efficiency of 50.09% from the route without the TSP method, which is 3,960 meters. Thus, it is expected that there will also be optimization of time and transportation costs in this delivery.